Organic-inorganic composite high-resistance layer of side glaze of zinc oxide resistor disc and preparation method of organic-inorganic composite high-resistance layer

By preparing an inorganic-organic composite high-resistivity layer on the side of zinc oxide resistors, the problems of insufficient high-temperature resistance, high-current impact resistance, and leakage current performance of the glaze material on the side of zinc oxide resistors were solved, achieving high bonding strength, low-temperature curing, and excellent insulation performance of the resistors.

CN119285378APending Publication Date: 2025-01-10ZHONGYUAN ENGINEERING COLLEGE
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411476609.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing zinc oxide resistor sheet side glaze materials have shortcomings in terms of high temperature resistance, high current impact resistance, and leakage current performance, especially the poor adhesion of epoxy glaze, easy cracking of glass glaze, and poor insulation of inorganic glaze.

Method used

An inorganic-organic composite high-resistivity layer is adopted. An inorganic coating is first prepared on the side of the zinc oxide resistor sheet, and then an organic coating is rolled onto its surface. Components such as aluminum salt, water-based epoxy resin, and polyamide resin are used, combined with a low-temperature calcination process to form a dense and uniform composite high-resistivity layer.

Benefits of technology

It significantly improves the resistance of the resistor sheet to high temperature, high current impact and leakage current, reduces the curing temperature, improves the bonding force and insulation performance with the resistor sheet blank, and enhances the shock resistance and anti-peeling ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a zinc oxide resistor disc side glaze organic-inorganic high-resistance layer and a preparation method thereof. The zinc oxide resistor disc side glaze organic-inorganic high-resistance layer comprises the following inorganic components in parts by weight: 10-20 parts of an aluminum salt component, 50-70 parts of an inorganic filler component, 10-30 parts of waterborne epoxy resin, 5-10 parts of distilled water and the like. The coating comprises the following organic components in parts by weight: 10-20 parts of epoxy resin, 3-5 parts of polyamide resin, 5-7 parts of JYM resin rubber powder, 3-5 parts of acrylic resin, 5-7 parts of organic silicon resin, 2-5 parts of a silane coupling agent, 1-5 parts of cyclohexanone and the like. The method comprises the following steps: roller-coating inorganic slurry on the surface of a resistor disc, performing low-temperature curing to obtain a uniform and compact inorganic high-resistance layer, roller-coating organic slurry on the surface of the formed inorganic coating, and performing curing to obtain an organic-inorganic composite high-resistance layer. The side glaze high-resistance layer has excellent performances of high temperature resistance, large current impact resistance, low leakage current and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an organic-inorganic high-resistance layer of zinc oxide resistor side glaze with excellent performance and a preparation method thereof, belonging to the technical field of resistor side glaze coating. Background Art

[0002] Zinc oxide resistors have excellent nonlinear volt-ampere characteristics, large current capacity and small leakage current, so they are often used as the core components of lightning arresters and are widely used in power systems. They can absorb the overvoltage energy of power transmission lines and limit the overvoltage amplitude, thereby effectively protecting electrical equipment from damage caused by overvoltages such as lightning.

[0003] The ability of a resistor to withstand large current impacts is one of its important characteristic parameters. When the duration of a pulsed large current is short, surface flashover damage will occur. Therefore, in order to improve the resistor's ability to withstand steep wave large current impacts, it is necessary to solve the surface flashover problem by roller coating the side insulation layer. At present, there are three main types of side insulation materials commonly used at home and abroad, namely epoxy glaze, glass glaze and inorganic high resistance layer.

[0004] Epoxy glaze is made of epoxy resin and curing agent with good insulation performance as the insulation matrix, and a certain amount of inorganic fillers, diluents and colorants are added. It is easy to mix with solids or other objects, has high adhesion and low shrinkage. In addition, it has excellent chemical stability, excellent resistance to various chemicals, low water absorption and excellent electrical insulation performance, which strengthens the side insulation strength to a certain extent. However, due to its poor adhesion and large difference in expansion coefficient with the valve plate, it is easy to produce defects such as micro cracks when subjected to thermal shock, resulting in a decrease in insulation performance, thus limiting its application range.

[0005] Glass glaze has strong insulation and stain resistance, and is an ideal side protection material. However, the expansion coefficient of glass glaze is inconsistent, and it is easy to crack or even fall off when the resistor is subjected to a large current impact. In addition, according to environmental protection requirements, lead-free glass glaze is generally used now, but the sintering temperature of most lead-free glass glazes is high, far exceeding the heat treatment temperature of the resistor, resulting in the performance degradation of the resistor, limiting its widespread use.

[0006] Inorganic side glaze is an insulating ceramic sintered at high temperature together with the resistor body. It has the characteristics of strong bonding and aging resistance. It can increase the short-wave discharge capacity and improve the moisture resistance, arc resistance and corona resistance without affecting the volt-ampere characteristics of the resistor itself. However, inorganic side glaze generally has the defect of poor insulation ability and weak hydrophobicity, which may reduce the insulation performance due to moisture absorption.

[0007] In order to improve the problems existing in the high-resistance layer of the glaze on the side of the resistor, a dense and uniform inorganic coating is first prepared on the side of the resistor, and then a new organic composite coating is roller-coated on the surface of the inorganic coating to obtain an organic-inorganic composite high-resistance layer with low curing temperature, high temperature resistance, high current shock resistance and lower leakage. Summary of the invention

[0008] The key technical problem to be solved by the present invention is to provide an organic-inorganic composite high-resistance layer of the side glaze of a zinc oxide resistor and a preparation method thereof, aiming to improve its performance in terms of high temperature resistance, resistance to large current impact and lower leakage current.

[0009] In order to solve the above-mentioned problems, the present invention provides the following technical solutions: An organic-inorganic composite high-resistance layer of zinc oxide resistor side glaze includes the following raw materials in parts by weight: Inorganic components: Aluminum salt component 10-20; Inorganic filler component 50-70; Waterborne epoxy resin component 10-30; Distilled water 5-10; Organic ingredients: Epoxy resin component 10-20; Polyamide resin components 3-5; JYM resin powder component 5-7; Acrylic resin components 3-5; Silicone resin components 5-7; Silane coupling agent components 2-5; 1-5 parts of cyclohexanone.

[0010] Furthermore, the aluminum salt component is one or two of aluminum phosphate, aluminum dihydrogen phosphate, aluminum chloride and aluminum oxide.

[0011] Furthermore, the inorganic filler component is one or two of mullite, black iron oxide and red iron oxide.

[0012] Furthermore, the model of the waterborne epoxy resin component is 387w; the epoxy resin component adopts one or two models of E-12 and E-44.

[0013] Furthermore, the polyamide resin component adopts one or both of PA12 and PPA with low molecular weight.

[0014] Furthermore, the acrylic resin component has a model number of 772A, and the silicone resin component has a model number of one or both of 3037 and 3074.

[0015] Furthermore, the silane coupling agent component adopts one or two of KH550, KH560 and KH602.

[0016] The present invention also provides a method for preparing the organic-inorganic composite high-resistance layer of the zinc oxide resistor side glaze, which comprises the following specific steps: a. After mixing the inorganic components in proportion, adding dispersant and water, grinding them evenly, roller coating them on the formed zinc oxide resistance layer, and calcining them to obtain the inorganic high resistance layer; b. After mixing the organic components in proportion, add dispersant and cyclohexanone, grind them evenly, and then roll-coat them on the inorganic coating that has been formed after the treatment in step a, and calcine to obtain an organic high-resistance layer.

[0017] Furthermore, in step a, the grinding time is 2-5 hours, and the ground slurry is roller-coated on the formed zinc oxide resistor with a thickness of 0.1-0.6 mm.

[0018] Furthermore, the calcination temperature in step a is 280-450° C. and the calcination time is 3-8 hours.

[0019] Furthermore, in step b, the grinding time is 3-7 hours, and the ground slurry is roller-coated on the surface of the inorganic coating of the resistor that has been sintered, with a thickness of 0.2-0.5 mm.

[0020] Further, the calcination temperature in step b is 170-230 o C, time is 2-5 h.

[0021] The typical preparation method of the organic-inorganic composite high resistance layer of the side glaze of the zinc oxide resistor of the present invention is as follows: 1. The formula is based on the mass percentage, and the specific components include: aluminum salt component: 10-20 parts, inorganic filler component: 50-70 parts, water-based epoxy resin component: 10-30 parts, distilled water 5-10 parts; 2. Weigh various raw materials according to the formula listed in "1" above, and then put them into a ball mill for wet grinding for 2-5 hours. Roll the ground slurry on the formed zinc oxide resistor with a thickness of about 0.1-0.6 mm. o After calcining at 3-8 hours, an inorganic high resistance layer is obtained; 3. The formula includes the following components by mass: epoxy resin component: 10-20 parts, polyamide resin component: 3-5 parts, JYM resin powder component: 5-7 parts, acrylic resin component: 3-5 parts, silicone resin component: 5-7 parts, silane coupling agent component: 2-5 parts, cyclohexanone 1-5 parts; 4. Weigh various raw materials according to the formula listed in "3", and then put them into a ball mill for wet grinding for 3-7 hours. Roll the ground slurry on the surface of the inorganic coating of the sintered resistor. The thickness is about 0.2-0.5 mm. After the roller coating is completed, put the resistor into a heating furnace and heat it for 2-5 hours. The temperature is controlled at 170-230 o C, thereby obtaining a high temperature resistant organic high resistance layer of the side glaze; Compared with the prior art, the organic-inorganic composite high-resistance layer of the zinc oxide resistor side glaze proposed in the present invention has the following advantages: 1. The inorganic high-resistance layer in the side glaze prepared by the method of the present invention has an aluminum salt adhesive that is very viscous and can be cured at a low temperature. Compared with the conventional side glaze preparation method, the curing temperature is greatly reduced, which is conducive to the stability of the zinc oxide resistor blank formula. At the same time, it has a strong bonding force with the blank, and the performance of anti-seismic, anti-stripping and high-temperature airflow erosion resistance is significantly improved.

[0022] 2. The organic high-resistance layer in the side glaze prepared by the method of the present invention is prepared by adding a polyamide resin component to replace the traditional polymer adhesive polyvinyl alcohol to prepare a zinc oxide resistor. The lubricity of a series of polymers such as polyamide resin is utilized to reduce the formation of bubbles in each process, improve the uniformity and density of the resistor, and thus improve the large current passing capacity of the resistor.

[0023] 3. After the composite treatment of inorganic high resistance layer and organic high resistance layer, the conventional performance of the resistor side glaze, such as high temperature resistance, resistance to large current impact and leakage current, etc., is significantly improved. DETAILED DESCRIPTION

[0024] The present invention will be further described below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention, and those skilled in the art in this field can make some non-essential improvements and adjustments based on the content of the above invention.

[0025] The mass fractions in the examples of the present invention and the comparative examples are all in g.

[0026] Example 1 The preparation method of the organic-inorganic composite high resistance layer of the side glaze of the zinc oxide resistor of this embodiment is as follows: 1. The formula is based on the mass percentage. The specific components include: aluminum dihydrogen phosphate component: 10 parts, iron oxide black component: 70 parts, 387w water-based epoxy resin component: 15 parts, distilled water: 5 parts; 2. Weigh various raw materials according to the above formula, and then put them into a ball mill for wet grinding for 3 hours. Roll the ground slurry onto the formed zinc oxide resistor with a thickness of 0.3-0.4 mm. oAfter calcination at 4 °C for 4 hours, an inorganic high resistance layer was obtained; 3. The formula is based on the mass percentage, and the specific components include: E-44 epoxy resin component: 15 parts, PPA polyamide resin component: 3 parts, JYM resin powder component: 5 parts, 772A acrylic resin component: 3 parts, 3074 silicone resin component: 7 parts, KH560 silane coupling agent component: 3 parts, cyclohexanone: 4 parts; 4. Weigh various raw materials according to the above formula, and then put them into a ball mill for wet grinding for 4 hours. Roll the ground slurry on the surface of the inorganic coating of the sintered resistor with a thickness of 0.2-0.4 mm. After roller coating, put the resistor into a heating furnace and heat it for 3 hours at a temperature of 190 o C, thereby obtaining a high temperature resistant organic high resistance layer of the side glaze.

[0027] Example 2 The preparation method of the organic-inorganic composite high resistance layer of the side glaze of the zinc oxide resistor of this embodiment is as follows: 1. The formula is based on the mass percentage, and the specific components include: alumina component: 12 parts, mullite component: 65 parts, 387w water-based epoxy resin component: 13 parts, distilled water: 10 parts; 2. Weigh various raw materials according to the above formula, and then put them into a ball mill for wet grinding for 3 hours. Roll the ground slurry onto the formed zinc oxide resistor with a thickness of 0.3-0.4 mm. o After calcination at 400 °C for 5 hours, an inorganic high-resistance layer was obtained; 3. The formula is based on the mass percentage, and the specific components include: E-12 epoxy resin component: 10 parts, PPA polyamide resin component: 4 parts, JYM resin powder component: 7 parts, 772A acrylic resin component: 5 parts, 3074 silicone resin component: 7 parts, KH560 silane coupling agent component: 4 parts, cyclohexanone: 3 parts; 4. Weigh various raw materials according to the above formula, and then put them into a ball mill for wet grinding for 5 hours. Roll the ground slurry on the surface of the inorganic coating of the sintered resistor with a thickness of 0.2-0.4 mm. After roller coating, put the resistor into a heating furnace and heat it for 3 hours at a temperature of 210 o C, thereby obtaining a high temperature resistant organic high resistance layer of the side glaze.

[0028] Example 3 The preparation method of the organic-inorganic composite high resistance layer of the side glaze of the zinc oxide resistor of this embodiment is as follows: 1. The formula is based on the mass percentage, and the specific components include: aluminum phosphate component: 15 parts, red iron oxide component: 55 parts, 387w water-based epoxy resin component: 23 parts, distilled water: 7 parts; 2. Weigh various raw materials according to the above formula, and then put them into the ball mill for wet grinding for 2-5 hours. Roll the ground slurry on the formed zinc oxide resistor with a thickness of 0.3-0.4 mm at 330 o After calcination at 400 °C for 6 hours, an inorganic high-resistance layer was obtained; 3. The formula is based on the mass percentage, and the specific components include: E-12 epoxy resin component: 12 parts, PA12 polyamide resin component: 5 parts, JYM resin powder component: 7 parts, 772A acrylic resin component: 4 parts, 3037 silicone resin component: 6 parts, KH602 silane coupling agent component: 4 parts, cyclohexanone: 2 parts; 4. Weigh various raw materials according to the above formula, and then put them into a ball mill for wet grinding for 4 hours. Roll the ground slurry on the surface of the inorganic coating of the sintered resistor with a thickness of 0.2-0.4 mm. After roller coating, put the resistor into a heating furnace and heat it for 4 hours at a temperature of 220 o C, thereby obtaining a high temperature resistant organic high resistance layer of the side glaze.

[0029] Example 4 The preparation method of the organic-inorganic composite high resistance layer of the side glaze of the zinc oxide resistor of this embodiment is as follows: 1. The formula is based on the mass percentage, and the specific components include: aluminum chloride component: 18 parts, mullite component: 37 parts, red iron oxide component: 20 parts, 387w water-based epoxy resin component: 17 parts, distilled water: 8 parts; 2. Weigh various raw materials according to the above formula, and then put them into the ball mill for wet grinding for 2-5 hours. Roll the ground slurry on the formed zinc oxide resistor with a thickness of 0.3-0.4 mm and grind at 360 o After calcination at 400 °C for 7 hours, an inorganic high-resistance layer was obtained; 3. The formula includes the following components by mass: E-12 epoxy resin component: 18 parts, PA12 polyamide resin component: 3 parts, JYM resin powder component: 5 parts, 772A acrylic resin component: 3 parts, 3037 silicone resin component: 5 parts, KH602 silane coupling agent component: 1 part, KH550 silane coupling agent component: 1 part, cyclohexanone: 4 parts; 4. Weigh various raw materials according to the above formula, and then put them into a ball mill for wet grinding for 4 hours. The ground slurry is roller-coated on the surface of the inorganic coating of the sintered resistor. The thickness is: 0.2-0.4 mm. After roller coating, the resistor is placed in a heating furnace and heated for 4 hours at a temperature of 230 o C, thereby obtaining a high temperature resistant organic high resistance layer of the side glaze.

[0030] Example 5 The preparation method of the organic-inorganic composite high resistance layer of the side glaze of the zinc oxide resistor of this embodiment is as follows: 1. The formula is based on the mass percentage, and the specific components include: aluminum chloride component: 20 parts, mullite component: 65 parts, 387w water-based epoxy resin component: 10 parts, distilled water: 5 parts; 2. Weigh various raw materials according to the above formula, and then put them into a ball mill for wet grinding for 2-5 hours. Roll the ground slurry onto the formed zinc oxide resistor with a thickness of 0.3-0.4 mm. o After calcination at 400 °C for 8 hours, an inorganic high-resistance layer was obtained; 3. The formula includes the following components by mass: E-12 epoxy resin component: 10 parts, E-44 epoxy resin component: 10 parts, PA12 polyamide resin component: 1 part, PPA polyamide resin component: 2 parts, JYM resin powder component: 5 parts, 772A acrylic resin component: 3 parts, 3037 silicone resin component: 1 part, 3074 silicone resin component: 4 parts, KH602 silane coupling agent component: 1 part, KH560 silane coupling agent component: 1 part, cyclohexanone: 2 parts; 4. Weigh various raw materials according to the above formula, and then put them into a ball mill for wet grinding for 4 hours. The ground slurry is roller-coated on the surface of the inorganic coating of the sintered resistor. The thickness is: 0.2-0.4 mm. After roller coating, the resistor is placed in a heating furnace and heated for 2 hours. The temperature is controlled at 180 o C, thereby obtaining a high temperature resistant organic high resistance layer of the side glaze.

[0031] Example 6 The preparation method of the organic-inorganic composite high resistance layer of the side glaze of the zinc oxide resistor of this embodiment is as follows: 1. The formula is based on the mass percentage. The specific components include: aluminum dihydrogen phosphate component: 14 parts, red iron oxide component: 50 parts, 387w water-based epoxy resin component: 30 parts, distilled water: 6 parts; 2. Weigh various raw materials according to the above formula, and then put them into the ball mill for wet grinding for 2-5 hours. Roll the ground slurry on the formed zinc oxide resistor with a thickness of 0.3-0.4 mm and heat at 450 o After calcination at 3 °C for 3 hours, an inorganic high-resistance layer was obtained; 3. The formula includes the following components by mass: E-12 epoxy resin component: 5 parts, E-44 epoxy resin component: 5 parts, PA12 polyamide resin component: 2 parts, PPA polyamide resin component: 3 parts, JYM resin powder component: 6 parts, 772A acrylic resin component: 4 parts, 3037 silicone resin component: 2 parts, 3074 silicone resin component: 3 parts, KH550 silane coupling agent component: 2 parts, KH560 silane coupling agent component: 3 parts, cyclohexanone: 5 parts; 4. Weigh various raw materials according to the above formula, and then put them into a ball mill for wet grinding for 4 hours. The ground slurry is roller-coated on the surface of the inorganic coating of the sintered resistor. The thickness is: 0.2-0.4 mm. After roller coating, the resistor is placed in a heating furnace and heated for 5 hours at a temperature of 170 o C, thereby obtaining a high temperature resistant organic high resistance layer of the side glaze.

[0032] Comparative Example 1 On the basis of Example 1, the inorganic component does not contain aluminum dihydrogen phosphate component, and the other steps are the same as Example 1. The specific method is as follows: 1. The formula is based on the mass percentage, and the specific components include: black iron oxide component: 80 parts, 387w water-based epoxy resin component: 15 parts, distilled water: 5 parts; 2. Weigh various raw materials according to the above formula, and then put them into a ball mill for wet grinding for 3 hours. Roll the ground slurry onto the formed zinc oxide resistor with a thickness of 0.3-0.4 mm. o After calcination at 4 °C for 4 hours, an inorganic high resistance layer was obtained; 3. The formula is based on the mass percentage, and the specific components include: E-44 epoxy resin component: 15 parts, PPA polyamide resin component: 3 parts, JYM resin powder component: 5 parts, 772A acrylic resin component: 3 parts, 3074 silicone resin component: 7 parts, KH560 silane coupling agent component: 3 parts, cyclohexanone: 4 parts; 4. Weigh various raw materials according to the above formula, and then put them into a ball mill for wet grinding for 4 hours. Roll the ground slurry on the surface of the inorganic coating of the sintered resistor with a thickness of 0.2-0.4 mm. After roller coating, put the resistor into a heating furnace and heat it for 3 hours at a temperature of 190 o C, thereby obtaining a high temperature resistant organic high resistance layer of the side glaze.

[0033] Comparative Example 2 On the basis of Example 1, the polyamide resin component is replaced by the polyvinyl alcohol component, and the other steps are the same as those of Example 1. The specific method is as follows: 1. The formula is based on the mass percentage. The specific components include: aluminum dihydrogen phosphate component: 10 parts, iron oxide black component: 70 parts, 387w water-based epoxy resin component: 15 parts, distilled water: 5 parts; 2. Weigh various raw materials according to the above formula, and then put them into a ball mill for wet grinding for 3 hours. Roll the ground slurry onto the formed zinc oxide resistor with a thickness of 0.3-0.4 mm. o After calcination at 4 °C for 4 hours, an inorganic high resistance layer was obtained; 3. The formula is based on the mass percentage, and the specific components include: E-44 epoxy resin component: 15 parts, PVA-217 polyvinyl alcohol component: 3 parts, JYM resin powder component: 5 parts, 772A acrylic resin component: 3 parts, 3074 silicone resin component: 7 parts, KH560 silane coupling agent component: 3 parts, cyclohexanone: 4 parts; 4. Weigh various raw materials according to the above formula, and then put them into a ball mill for wet grinding for 4 hours. Roll the ground slurry on the surface of the inorganic coating of the sintered resistor with a thickness of 0.2-0.4 mm. After roller coating, put the resistor into a heating furnace and heat it for 3 hours at a temperature of 190 o C, thereby obtaining a high temperature resistant organic high resistance layer of the side glaze.

[0034] Comparative Example 3 On the basis of Example 1, no organic high resistance layer is prepared, and other steps are the same as Example 1. The specific method is as follows: 1. The formula is based on the mass percentage. The specific components include: aluminum dihydrogen phosphate component: 10 parts, iron oxide black component: 70 parts, 387w water-based epoxy resin component: 15 parts, distilled water: 5 parts; 2. Weigh various raw materials according to the above formula, and then put them into a ball mill for wet grinding for 3 hours. Roll the ground slurry onto the formed zinc oxide resistor with a thickness of 0.3-0.4 mm. o After calcination at 4 °C for 4 hours, an inorganic high resistance layer was obtained; Comparative Example 4 On the basis of Example 1, the inorganic high-resistance layer is not prepared, and the other steps are the same as those of Example 1. The specific method is as follows: 1. The formula is based on the mass percentage. The specific components include: E-44 epoxy resin component: 15 parts, PPA polyamide resin component: 3 parts, JYM resin powder component: 5 parts, 772A acrylic resin component: 3 parts, 3074 silicone resin component: 7 parts, KH560 silane coupling agent component: 3 parts, cyclohexanone: 4 parts; 2. Weigh various raw materials according to the above formula, and then put them into a ball mill for wet grinding for 4 hours. Roll the ground slurry on the formed zinc oxide resistor with a thickness of 0.2-0.4 mm. After roller coating, put the resistor into a heating furnace and heat it for 3 hours at a temperature of 190 o C, thereby obtaining a high temperature resistant organic high resistance layer of the side glaze.

[0035] The electrical insulation performance (leakage current, large current impact test) of the insulating coating prepared in Examples 1-3 was tested using the Φ28*30 resistor blank produced by the manufacturer as the substrate. The results are shown in Table 1.

[0036] Table 1 Test results of electrical insulation performance of insulating coatings in the examples

[0037] As can be seen from Table 1, the inorganic-organic double-coating side glaze insulating coating prepared by the formula and process provided by the present invention, the resistor samples prepared according to Examples 1, 2, and 3 have low leakage current, and the 4 / 10 μs large current impact performance is stable. After multiple batches of measurements, the Φ28*30 resistor successfully passed the 4 / 10 μs, 65 KA amplitude multiple impact test, and the large current resistance capability met the requirements; leakage current level: the leakage current of the Φ28*30 resistor is less than 7 μA, the leakage current change does not exceed 2 μA, and the leakage current level meets the requirements.

[0038] Taking the resistor blank of size Φ28*30 produced by the manufacturer as the substrate, the test results of the electrical insulation performance (leakage current, large current impact test) of the insulating coating prepared in Example 1 and Comparative Examples 1-4 are shown in Table 2.

[0039] Table 2 Test results of electrical insulation performance of insulating coating of control example

[0040] Table 2 shows that the test results of the electrical insulation properties (leakage current, large current impact test) of the insulating coating prepared in Example 1 and Comparative Example 1 show that when the aluminum salt component is used as the adhesive, it has a strong bonding force with the resistor valve body, and the performances such as anti-vibration, anti-stripping and high-temperature airflow erosion resistance are significantly improved, and it can be cured at low temperature. Compared with the conventional side glaze preparation method (curing temperature above 1000°C), the curing temperature is greatly reduced, which is conducive to the stability of the zinc oxide resistor body formula.

[0041] The test results of the electrical insulation properties (leakage current, large current impact test) of the insulating coatings prepared in Example 1 and Control Example 2 show that when polyamide resin components are used instead of polyvinyl alcohol as the polymer binder for preparing zinc oxide resistors, the uniformity and density of the high resistance layer of the resistor are significantly improved, thereby improving the large current passing capacity of the resistor.

[0042] The test results of the electrical insulation performance (leakage current, large current impact test) of the insulating coating prepared in Example 1 and Control Examples 3-4 show that compared with the use of a single inorganic high-resistance layer and an organic high-resistance layer, when the resistor uses an inorganic-organic composite high-resistance layer, there is no side flash or glaze falling during the test process, and the overall conventional properties of the resistor side glaze such as high temperature resistance, large current impact resistance and leakage current are significantly improved.

[0043] The implementation of the present invention can solve the practical problems in the actual production of resistors, and the inorganic-organic composite coating method is used to comprehensively solve the problems of adhesion between the side coating material and the zinc oxide resistor body, insulation, high current resistance, temperature resistance, etc. The expansion coefficient of the inorganic coating material is close to the inorganic insulating coating of the zinc oxide resistor body. The coating has strong adhesion with the body, expands with the body after heating, improves the heat resistance, and plays an excellent protective performance against lightning pulses or overvoltage. The uniformity and density of the resistor are improved by adding the lubricity of a series of polymers such as polyamide resin, thereby improving the large current passing capacity of the resistor. The inorganic coating and the organic coating have good adhesion, the composite insulating coating has a good charged life, and has excellent protection against surges such as lightning strikes and overvoltages; the prepared product and the preparation process are environmentally friendly and green, the raw materials used do not contain toxic substances such as lead, and do not use highly toxic organic solvents such as toluene; during manufacturing and when discarded after use, no pollution is caused to the environment, so it has huge potential social and economic benefits and broad application prospects.

[0044] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. An organic-inorganic composite high resistance layer of zinc oxide resistor side glaze, characterized in that: Including the following raw materials in parts by weight: Inorganic components: Aluminum salt component 10-20; Inorganic filler component 50-70; Waterborne epoxy resin component 10-30; Distilled water 5-10; Organic ingredients: Epoxy resin component 10-20; Polyamide resin components 3-5; JYM resin powder component 5-7; Acrylic resin components 3-5; Silicone resin components 5-7; Silane coupling agent components 2-5; 1-5 parts of cyclohexanone.

2. The organic-inorganic composite high resistance layer of the zinc oxide resistor side glaze according to claim 1, characterized in that: The aluminum salt component is one or two of aluminum phosphate, aluminum dihydrogen phosphate, aluminum chloride and aluminum oxide.

3. The organic-inorganic composite high resistance layer of the zinc oxide resistor side glaze according to claim 1, characterized in that: The inorganic filler component is one or two of mullite, black iron oxide and red iron oxide.

4. The organic-inorganic composite high resistance layer of the zinc oxide resistor side glaze according to claim 1, characterized in that: The model of the waterborne epoxy resin component is 387w; the epoxy resin component adopts one or both of the models E-12 and E-44; the polyamide resin component adopts one or both of the models PA12 or PPA with low molecular weight.

5. The organic-inorganic composite high resistance layer of the zinc oxide resistor side glaze according to claim 1, characterized in that: The acrylic resin component is of model 772A, the silicone resin component is of model 3037 or 3074 or both; the silane coupling agent component is of model KH550, KH560 or KH602 or both.

6. The method for preparing the organic-inorganic composite high resistance layer of the zinc oxide resistor side glaze according to any one of claims 1 to 5, characterized in that: The specific steps are: a. Mix the inorganic components according to the proportion, grind them evenly, and then roll-coat them on the formed zinc oxide resistance layer, and calcine them to obtain the inorganic high resistance layer; b. Mix the organic components in proportion, grind them evenly, and then roll-coat them on the inorganic coating that has been formed after the treatment in step a, and calcine them to obtain an organic high-resistance layer.

7. The method for preparing the organic-inorganic composite high resistance layer of the zinc oxide resistor side glaze according to claim 6, characterized in that: The grinding time in step a is 2-5 hours, and the ground slurry is roller-coated on the formed zinc oxide resistor with a thickness of 0.1-0.6 mm.

8. The method for preparing the organic-inorganic composite high resistance layer of the zinc oxide resistor side glaze according to claim 6, characterized in that: The calcination temperature in step a is 280-450° C. and the calcination time is 3-8 hours.

9. The method for preparing the organic-inorganic composite high resistance layer of the zinc oxide resistor side glaze according to claim 8, characterized in that: The grinding time in step b is 3-7 hours, and the ground slurry is roller-coated on the surface of the inorganic coating of the resistor that has been sintered, with a thickness of 0.2-0.5 mm.

10. The method for preparing the organic-inorganic composite high resistance layer of the zinc oxide resistor side glaze according to claim 8, characterized in that: The calcination temperature in step b is 170-230 o C, time is 2-5 h.

Citation Information

Patent Citations

  • Preparation method of inorganic-organic composite insulation coating resistant to large current impact

    CN102503582A

  • Preparation method of inorganic insulating coating based on synergistic cooperation of inorganic high-resistance layer and low-temperature glass glaze

    CN112694348A

  • Voltage nonlinear resistor and its producing method

    CN1290943A

  • Coating composition with high insulation on siliconsteel sheets and silicon steel sheet havinginsulation film formed therefrom

    KR1020030013052A

  • Method for coating a conductive material

    US4036721A